INTEGRASI SISTEM INFORMASI PUSKESMAS - Muljo, Hery Harjono; Darmadi, Herru (Bina Nusantara University, 2009)
The aim of integrating the information system for Community Health Center is to create an integrated information system for managing all data processing between different community health centers, namely district community health centers with village community health centers. Methods used in integrating community health center information system are Identifying Information Requirements, Identifying System Requirements, Modification of Information System Application Design (integrated), Modification of Information System Application, Application Test, Refining Application, employee training, and the last is implementation of integrated community health center information system. The result of this research is development of integrated community health center information system which in the past is only integrated in the same location, and now integrates between community health centers in different locations. The steps are development of database from local database into distributed and central database; development of admission transaction, clinic data, and pharmacy data modules which makes it possible for synchronization of patient data between distributed database with the central database. Therefore, patient data is still stored in both databases.Keywords: integration, information system, community health center